The Relationship Between Confirmed COVID-19 Positive Characteristics of Laboring Mothers and the Incidence of Asphyxia in Infants at Hospital Dr. Hasan Sadikin Bandung - Triyani, Dinna; Yogi Pramatirta, Akhmad; Aryuti Nirmala, Sefita; Indra Susanti, Ari; Dyah Bestari, Astuti (Jurnal Ilmiah Kesehatan, 2024)
The Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is the cause of Coronavirus Disease 2019 (COVID-19). In December 2021, the Omicron variation was first identified in Indonesia, and it has since been linked to nearly 72 million cases worldwide. When COVID-19 is present during pregnancy, unfavorable outcomes including stillbirth, preterm delivery, and maternal mortality may occur. The purpose of this research was to examine the association between the features of women who tested positive for COVID-19 and the incidence of asphyxia in their babies at Dr. Hasan Sadikin General Hospital in Bandung between July 2021 and July 2022. A quantitative descriptive technique was used, and 69 mothers and 70 babies were sampled overall. Medical records provided the data, which was then subjected to chi-square analysis. There was no discernible correlation between the incidence of hypoxia and the mother's age (p = 0.838), parity (p = 0.647), or delivery method (p = 0.313). Nonetheless, a noteworthy correlation was seen between the gestational age (p = 0.001) and the maternal difficulties (p = 0.013) associated with baby hypoxia. This research found that whereas age, parity, and delivery style were not substantially linked with newborn hypoxia, gestational age and COVID-19-related problems were.